고령임부 대상 모바일 웹 기반 임신 건강관리 교육프로그램 효과 - 왕희정; 김일옥; Wang, Hee Jung; Kim, Il Ok (Journal of Korean Academy of Nursing, 2015)
Purpose: This study was conducted to develop a mobile web-based pregnancy health care educational program for mothers who were at an advanced maternal age (AMA) and to verify the effects of the program on pregnancy health care. Methods: This program was developed using a web-based teaching-learning system design model and composed of 10 subject areas. This research was a quasi-experimental study using a non-equivalent control group pretest-posttest time serial design and data were collected from April 2 to May 3, 2014. To verify the effects of the program, it was used for 2 weeks with 30 AMA mothers (experimental group). For the control group, a classroom education booklet for pregnant women used with 31 AMA mothers. Results: The experimental group having participated in program had statistically significantly higher scores for knowledge (t=3.76, p <.001), self-efficacy (t=8.54, p <.001), and practice behavior (t=4.88, p <.001) of pregnancy health care, compared to the control group. Conclusion: The results of the program indicate that a Mobile web-based pregnancy health care educational program is effective in meeting the needs of AMA mothers and can be used as the prenatal educational program for AMA mothers and is appropriate as an educational media for theses mothers.